2021
DOI: 10.21203/rs.3.rs-509141/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Orbital torque in magnetic bilayers

Abstract: The spin Hall effect describes an electric-field-induced generation of spin currents through spin-orbit coupling. Since the spin-orbit coupling alone cannot generate the angular momentum, there must be a more fundamental process of the spin Hall effect. Theories suggested that an electric-field-induced generation of orbital currents, called orbital Hall effect, is the fundamental process, and spin currents are subsequently converted from orbital currents. Despite its fundamental importance, the orbital Hall ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Since η FM originates from the spin-orbit coupling, or more precisely the spin-orbit correlation near the Fermi energy, in the FM layer 22 , the orbital torque is sensitive to the electronic structure of the FM layer 21 . Among the conventional 3d FMs, Ni is predicted to have the strongest spin-orbit correlation near the Fermi energy 31 . The strong spin-orbit correlation in Ni is consistent with it's strong spin and anomalous Hall effects, transport phenomena that also arise from the spin-orbit coupling 35,36…”
Section: Evidence and Characteristics Of Orbital Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Since η FM originates from the spin-orbit coupling, or more precisely the spin-orbit correlation near the Fermi energy, in the FM layer 22 , the orbital torque is sensitive to the electronic structure of the FM layer 21 . Among the conventional 3d FMs, Ni is predicted to have the strongest spin-orbit correlation near the Fermi energy 31 . The strong spin-orbit correlation in Ni is consistent with it's strong spin and anomalous Hall effects, transport phenomena that also arise from the spin-orbit coupling 35,36…”
Section: Evidence and Characteristics Of Orbital Transportmentioning
confidence: 99%
“…In the FMs, the angular momentum of the injected spin and orbital currents is transferred to the local spins, giving rise to torques on the magnetization: spin and orbital torques 22 . Recent experimental studies have suggested the presence of the current-induced orbital torque [25][26][27][28][29][30][31][32][33] . However, the observed torque efficiency is much lower than the spin counterpart despite the fundamental role of the orbital response in the angular momentum transport.…”
mentioning
confidence: 99%
“…The orbital current is similar to the spin current in many ways because both orbital angular momentum (OAM) and spin transform in the same way under symmetry operations. Thus, experiments so far have focused on light element systems where the spin current contribution is expected to be negligible [29][30][31][32][33][34], or systems where the orbital and spin currents compete with each other and are opposite in sign [33,35,36]. Although these experiments imply the presence of the orbital current, which can hardly be explained by the spin current picture, they are far from being "direct" confirmations of the orbital current.…”
mentioning
confidence: 99%
“…As a surprise, recent studies accumulated evidence that the dynamics and transport of the orbital information can be released under the external stimuli such as electric field in many materials. Similar to those in spintronics, orbital current can carry the orbital angular moment originated from orbital Hall effect [494][495][496] and orbital Rashba effect [497][498][499][500][501], and exert torques on the magnetization. Hence, the orbitronics may provide another route to manipulate and detect magnetization.…”
Section: Orbital Angular Momentummentioning
confidence: 98%